Fundamental concepts of molecular spectroscopy - Bhuyan, Abani K. (Boca Raton : CRC press, 2023)
This practical textbook explains the core areas of molecular spectroscopy as a classical teacher would. The author explores and explains each concept, walking side by side with the student through carefully constructed text, pedagogy, and derivations to ensure comprehension of the basics before approaching higher level topics.
Includes Bibliography and index
Keywords: Nuclear magnetic resonance spectroscopy; Electron paramagnetic resonance; Raman spectroscopy; Molecular Eigenstates